"Sendwòm Gran Sè": The older sister syndrome. (27th March 2023) - Francois, Ericka
Abstract: Ericka Francois, an advocate for young people living in and aging out of foster care, thoughtfully shares the events that led to her and her siblings being placed in the child welfare system. Her frank account of physical abuse over the course of her early years of life illustrates the struggles many families face. Her and her siblings' entry into the child welfare system, an intervention intended to improve well‐being for her and siblings, produced varied outcomes. Ericka describes her blossoming in her grandmother's care and the pain of watching her siblings languish and even decline while in the state's care. Ericka makes a powerful appeal for immediate system changes. Key points for the family court community: Toxic parents can negatively affect children throughout their lifespan, and the children must heal themselves. A contrast on how unfit mothers can be compared to the worldwide "nurturing" and "caring" mother narrative. You can be traumatized from both generational trauma and the New York City foster care system. Without the right support, traumatized children cannot thrive as young adults. Parents do not deserve grace simply because they are parents. They deserve to educate themselves on how to be the best parents they can be this is a choice they made.